DESIGN, FABRICATION AND CHARACTERISATION OF FREE-STANDING THICK-FILM PIEZOELECTRIC CANTILEVERS FOR ENERGY HARVESTING - Kok, Swee Leong; White, Neil; Harris, Nick (LAP LAMBERT Academic Publishing, 2011)
Research into energy harvesting from ambient vibration sources has attracted great interest over the last few years, largely due to the rapid development in the areas of wireless technology and low power electronics. One of the mechanisms for converting mechanical vibration to electrical energy is the use of piezoelectric materials, typically operating as a cantilever in a bending mode, which generate a voltage across the electrodes when they are stressed. Traditionally, the piezoelectric materials are deposited on a non-electro-active substrate and are physically clamped at one end to a rigid base, which serves as a mechanical supporting platform. In this research, a three dimensional thick-film structure in the form of a free-standing cantilever incorporated with piezoelectric materials is proposed. The advantages of this structure include minimising the movement constraints on the piezoelectric, thereby maximising the electrical output and offering the ability for integration with other microelectronic devices. A series of free-standing composite cantilevers in the form of unimorphs were fabricated and characterised for their mechanical and electric properties. The unimorph structure consists of a pair of silver/palladium (Ag/Pd) electrodes sandwiching a laminar layer of lead zirconate titanate (PZT). An extended version of this unimorph, in the form of multimorph was fabricated to improve the electrical output performance, by increasing the distance of the piezoelectric layer from the neutral axis of the structure. This research also discusses the possibility of using an array of free-standing cantilevers in harvesting vibration energy in a broader bandwidth from an unpredictable ambient environment.